Elements of loadbearing brickwork. - Lenczner, David (International series of monographs in civil engineering, 1972)
Elements of Loadbearing Brickwork focuses on the developments in brickwork design and construction. Organized into seven chapters, this book first discusses the manufacture and properties of bricks. Subsequent chapters describe the properties of mortars and brickwork; design of brickwork members; reinforced brickwork; and composite action of loadbearing walls under wind loads. The last chapter presents the development in brickwork technology. This book will be valuable for students of structural engineering, building and architecture.